Importance of practical surgical training in increasing knowledge and skills in surgical fields among medical students on the example of the First National Polish Surgical Summerschool - Golebiowska, Maria; Chudzik, Robert; Sławiński, Mirosław; Gołębiowska, Beata; Jarosz, Katarzyna (Journal of Education, Health and Sport, 2017)
Medical students often choose surgical disciplines for their dream career. Surgery, which is both science and art, requires not only theoretical but also essential practical training, necessary in the correct surgical technique and consequently lower complications after surgery. Medical curriculum worldwide takes into account only a small number of practical surgical classes, which, apart from the ability to observe surgery and surgical procedures, makes it impossible to fully understand the surgical reality and to test the basic skills. The aim of the study is to present the validity of intensive practice courses in order to increase the knowledge and skills of surgical students among medical students. The study included measuring the level of knowledge of medical students before and after training on the practical aspects of surgical surgical practice. The measurement was carried out with the author's 40 questions questionnaire, whose distribution depended on the number of hours devoted to the given field. The study also monitored the timing and aesthetics of the stitches first two days and day four. The level of satisfaction with the course and the level of confidence and satisfaction in the acquired skills and knowledge were also measured. The study confirms the validity of conducting intensive practice courses in the field of surgical disciplines, both in terms of increased knowledge and improvement of objective and subjective characteristics of procedures performed.